Policing technology-facilitated domestic abuse (TFDA): views of service providers in Australia and the United Kingdom - Douglas, Heather (Journal of family violence, 2025)
Purpose: Technology-facilitated domestic abuse (TFDA) is a prevalent form of domestic abuse. While police are recognized as critical first responders to intimate partner violence, there is limited research about what the challenges to policing TFDA are perceived to be and how they might be addressed. This article speaks to this issue. Methods: Between April 2020 and June 2022, n = 196 Australian and n = 256 United Kingdom representatives of services engaged with domestic abuse victim-survivors participated in an online survey about TFDA. Survey components asked respondents to report on challenges to policing TFDA. The authors analyzed these comments. Results: Key themes identified from the survey responses regarding challenges to policing TFDA include that participants held perceptions that (a) police do not recognize TFDA as an aspect of coercive control and thus do not recognize its seriousness, (b) police receive inadequate training about TFDA, (c) police have insufficient time and personnel to tackle TFDA and (d) evidence collection is an obstacle to policing TFDA. Conclusions: The study points to a need to address the perceived concerns associated with policing TFDA to effectively respond to domestic abuse in the digital age and ensure domestic abuse perpetrators who misuse emerging technologies are held accountable.